Penerapan Algoritma RAITA pada Kamus Akronim Bahasa Indonesia Berbasis Android - Harahap, Annisa Fitri; Ginting, Guidio Leonarde (TIN: Terapan Informatika Nusantara, 2020)
Indonesian is the language of Malay which is used as the official language of the Republic of Indonesia and the language of the unity of the Indonesian nation. The Indonesian language was inaugurated after the Proclamation of Indonesian Independence, to be precise the day after, at the same time as the enactment of the constitution. Indonesian as the language of unity and the language of the State in the Unitary State of the Republic of Indonesia has a very dominant function in all aspects of social life. An acronym is an abbreviation in the form of a combination of letters or syllables or other parts that are written and pronounced as normal words. Acronyms, also called abbreviations, are short for a term which can be a combination of prefixed terms. Thus, an acronym stands for a term or name that is pronounced as a single word. Indonesian acronyms have a very large number of words, in general currently Indonesian acronyms are still in printed book form. The problem that is often faced by acronym dictionary users in the form of printed books is the difficulty in obtaining search results for Indonesian acronym words quickly and precisely because it must be done by opening each sheet of the book to find the acronym word being searched for. To overcome the problems described above, in this study the authors designed an Android-based Indonesian acronym application. In order to make it easier to get search results on the designed Indonesian acronym application, the authors apply the Raita algorithm in the search feature. The Raita algorithm is part of the exact string matching algorithm, which is the matching of strings precisely to the arrangement of characters in the matched string which has the same number and sequence of characters in the string. Raita designed an algorithm by comparing the last character of the pattern starting from the rightmost character from the "window".